Wielkopolska wczoraj i dziś - Matyaszczyk, Dorota (Wydział Prawa i Administracji UAM, 1992)
Over the ages, Wielkopolska had been a uniform entity from the cultural, immigration and legal points of view. This structure was destroyed only by the 1815 partition of Poland, when Wielkopolska was divided between Prussia and Russia. In common understanding, the territory of Wielkopolska is limited to the former Prussian dominion, with Northern border along the Noteć river and Eastern border along t h e Prosną river. However, hardly anybody remembers that Northern territories (Wałcz and Nakło regions) and Southern territories (Wschowa region) for many ages were the integral parts of Wielkopolska. The area of Wielkopolska changed with the changes in political situation of the state. Wielkopolska occupied t h e largest area after 1945, when it comprised ca. 40.000 km and included a part of regamed Territories, inhabited both by immigrants from Eastern temtories of Poland as well as the immigrants from the Poznań province. In 1950 Zielona Góra province was created; in consequence for the first part in the Polish history Western border of Wielkopolska was not the border of t h e state. The unfortunate administrative reform of 1975, which divided Poland into 49 provinces, introduced the widest changes into a historically shaped area of Wielkopolska. Former Wielkopolska was divided into 5 provinces. However, the memories about belonging to Wielkopolska are still vivid. It was proved by questionnaire research carried out by the author in 1992 in 384 communes from the area of 8 provinces which formerly belonged, partly or wholly, to Wielkopolska. One of t h e gestions pertained to the choice of the territory to which a given commune would like to belong fi new administrative division of the state were introduced. From among 319 answers (84%), 213 communes indicated Wielkopolska, and 5 answered that Wielkopolska is their likely choice. In this way a former Wielkopolska region in its pre-1975 borders was reconstructed; moreover, included the area which belonged to Wielkopolska between 1945 and 1950, as well as the area of southern and central parts of former Bydgoszcz Regency from the period 1815-1938.
Wielkopolska yesterday and today